Achieving Universal Health Coverage by Focusing on Primary Care in Japan: Lessons for Low- and Middle-Income Countries - Naoki Ikegami (Kerman University of Medical Sciences, 2016)
When the Japanese government adopted Western medicine in the late nineteenth century, it left intact the infrastructure of primary care by giving licenses to the existing practitioners and by initially setting the hurdle for entry into medical school low. Public financing of hospitals was kept minimal so that almost all of their revenue came from patient charges. When social health insurance (SHI) was introduced in 1927, benefits were focused on primary care services delivered by physicians in clinics, and not on hospital services. This was reflected in the development and subsequent revisions of the fee schedule. The policy decisions which have helped to retain primary care services might provide lessons for achieving universal health coverage in low- and middle-income countries (LMICs).